The Femicide in Indonesia: Critical Analysis and Innovative Legal Reconstruction - Ainal Mardhiah; Rizanizarli Rizanizarli; Iskandar A. Gani; Sri Walny Rahayu; Mohammad Nasr Khater (Unissula, 2026)
The purpose of this study is to examine the legal vacuum surrounding femicide in Indonesia and to urge legal reform to address this most extreme form of gender-based violence. Femicide, the killing of women for gender reasons, is not explicitly recognized in Indonesian positive law and is still processed under general murder provisions, thus ignoring the structural and gender dimensions of the crime. The research method used is a normative juridical method as well as a conceptual and comparative approach. The results of the study show that although femicide cases are increasing and judges are starting to consider gender motives as an aggravating factor, the absence of specific regulations leads to inconsistent legal protection and opens up opportunities for impunity. This article proposes three forms of legal reconstruction: the creation of a specific femicide crime or its recognition as an aggravating factor, the development of gender-based sentencing guidelines, and the development of technical judicial guidelines that ensure contextual interpretation of gender-based violence. These reforms are necessary to achieve substantive justice, legal certainty, and fulfill Indonesia's constitutional and international obligations to eradicate violence against women.